(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Multiculturalism, although initially viewed as a progressive discourse, have recently attracted the attention of many cultural theorists and academic commentators who tend to see it as conservative and following a reactionary dialectics. Political multiculturalism is often directed to subvert the monistic essentialities of nationality, for instance, the notion of Britishness or Indianness which persists through strict cultural homology of shared experiences. Multiculturalists, in this context, emphasised internal differentiation and shifting positionalities evolving new definition of national belonging deconstructing their constructivist ideologies. The present paper seeks to address the issue of how being entangled between fundamentalism and liberalism, between the Western culture and Indian ways of living, Shahid, the protagonist of the novel, The Black Album, finds himself in between the contradicting polarities of uncertainties that accentuate the search for his true identity.